EFEKTIVITAS PEMANFAATAN DANA BOS DI SEKOLAH - man, Herman man (Makassar Journal of Social Sciences, 2013)
This study aims to determine the effectiveness of the utilization of fund school operating costs ( BOS ). The population in this study is the overall head of the schools at the basic education level elementary and junior high school and the sample was 20% of the number of elementary and junior high schools in the city of Makassar. The type of data analyzed is secondary data that is in the form of the document reports a year-long BOS LPJP made quarterly. Data analysis technique used is qualitative analysis. The results of data analysis use BOS funds in schools should be based on agreements and joint decision between BOS School Management Team, Board of Teachers, and School Committee should be listed as one source of revenue in RKAS / budgets, in addition to the funds obtained from the local government or other sources legitimate. The agreement use of the funds (and other funds such ) should be put in writing in the form of meeting minutes are attached to the signature of all participants who attended the meeting. From all the BOS funds received by schools, schools are required to use some of those funds to buy textbooks or replace damaged. Books must be purchased at the primary level is the book subjects Religious Education, and Arts subjects and skills, while the junior level is the book of Social Sciences subjects and subjects of Information and Communication Technology. Use of the funds for transportation and money tired for civil service teachers are allowed only in the course of a school activity other than the obligation of teaching hours. Magnitude or unit costs for transportation and money tired civil servant teachers on duty outside the teaching hours be within reasonable limits. Local Government shall issue a regulation on the acceptable limit in each area taking into account socio-economic factors, geographical factors and other factors